Urban governance for sustainable global development: from the SDGs to the New Urban Agenda - Eva Dick (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
“Our struggle for global sustainability will be lost or won in cities.” With these words Ban Ki-moon, Secretary-General of the United Nations, opened the High-Level Delegation of Mayors and Regional Authorities in New York City on 23 April 2012. A little more than three years later, at the United Nations (UN) Summit in 2015, the 2030 Agenda for Sustainable Development was adopted. In the Agenda, 17 Sustainable Development Goals (SDGs) define the key areas and mech-anisms for a future global development partnership. One of these goals (SDG 11: “Make cities and human settlements inclusive, safe, resilient and sustainable”) distinctly alludes to urban development. The urban community has widely celebrated the adoption of this “stand-alone urban goal”. The step is perceived as reflecting an increased awareness of the important role of cities for global development pathways. Although sharing in this positive assessment, this briefing paper ar¬gues that for an effective follow-up to Agenda 2030, issues of urban and local governance ought to be addressed in further detail and as cross-cutting issues. This applies to the “urban” SDG 11, which does not have a distinct target on (good) governance. It is also true for the “governance” goal, SDG 16, which, while referring to institutions “at all levels”, does not spell out local or urban responsibilities. And it is pertinent for many sectoral goals, such as SDGs 13 (action towards climate change) and 9 (build resilient infrastructure), both of which strongly hinge on local- or city-level implementation. Against this background, the briefing paper identifies urban governance issues that are presently neglected in the SDGs and require further elaboration. This may occur in the process of the supplementary methodological work envisaged by the Inter-Agency and Expert Group on Sustainable Development Goal Indicators for the coming months (UN Economic and Social Council, 2016, p. 9). Even more importantly, the task of concretising the urban governance dimension – and thereby easing SDG implementa-tion – must also be related to other global policy processes and events. Notably the New Urban Agenda (NUA), which is to be formulated at the 2016 World Conference on Housing and Sustainable Urban Development (Habitat III) in Quito, Ecuador, from 17–20 October 2016, can be considered a key vehicle in this regard. Following are three decisive urban governance dimensions to be focussed on in the NUA: Urban governance frameworks: Since urban governance is exercised at different governmental levels, defining the roles and responsibilities of – and coordination between – these levels is essential. Decisive elements are national urban policies among other institutional frameworks; multi-level and -sectoral cooperation and coordination mechanisms; and formal and informal linkages beyond city borders. Intra-urban partnerships: Effective partnerships and co¬oper¬ative practices between local authorities, the private sector and civil society constitute the backbone of good urban governance. In particular, mechanisms and space for the participation of disadvantaged groups in collaboration and decision-making processes must be defined and the related capacities built. Transformative urban governance: In order to effectively confront global challenges in the sense of truly transformative development, key elements of climate-friendly governance at the city level must be defined, relating to both mitigation and adaptation measures.
Keywords: 330; Governance; Agenda 2030